2015
DOI: 10.1111/jsm.12899
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity in Patients with Dhat Syndrome: A Nationwide Multicentric Study

Abstract: Introduction There are limited numbers of studies on Dhat syndrome. Major limitations of the existing literature are heterogeneous assessment methods used to describe the comorbidity and small sample size from isolated centers. Aim To assess comorbidity with a common methodology in patients with Dhat syndrome from multiple centers across India. Methods Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 6 publications
1
38
0
Order By: Relevance
“…A recent multi-centric study from India reveals sexual dysfunction to be the most common co-morbidity (present in more than 50% of the patients) with Dhat syndrome followed by depression and neurotic or somatoform disorders. 7 One third of patients in this study did not report any other symptoms of psychiatric illness other than Dhat syndrome. 7 A recent review of world literature suggests depressive and anxiety disorders being the most common co-morbid psychiatric disorders with Dhat syndrome.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…A recent multi-centric study from India reveals sexual dysfunction to be the most common co-morbidity (present in more than 50% of the patients) with Dhat syndrome followed by depression and neurotic or somatoform disorders. 7 One third of patients in this study did not report any other symptoms of psychiatric illness other than Dhat syndrome. 7 A recent review of world literature suggests depressive and anxiety disorders being the most common co-morbid psychiatric disorders with Dhat syndrome.…”
Section: Introductionmentioning
confidence: 62%
“…7 One third of patients in this study did not report any other symptoms of psychiatric illness other than Dhat syndrome. 7 A recent review of world literature suggests depressive and anxiety disorders being the most common co-morbid psychiatric disorders with Dhat syndrome. 5 A detailed description of psychiatric co-morbidity is always desirable in view of the consideration of Dhat syndrome as an independent psychiatric diagnostic entity.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Previous studies on Dhat syndrome have also reported high rates of comorbid axis-I disorder and sexual dysfunction (Behere and Natraj, 1984;Bhatia and Malik, 1991;Chadda and Ahuja, 1990;Grover et al, 2014Grover et al, , 2015Nakra et al, 1977). However these studies have specifically not looked at the sequence of onset of symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…A recent multicentric study evaluated the prevalence of comorbid disorders in patients with Dhat syndrome and identified comorbid depressive disorders in one-fifth and comorbid anxiety disorders in another one-fifth of the patients. However, half of the patients had comorbid sexual dysfunction (Grover et al, 2015). However, none of these studies have reported the relationship of these comorbid disorders with symptoms of Dhat syndrome with respect to the fact that whether these precede the onset or follow the onset of Dhat syndrome.…”
Section: Introductionmentioning
confidence: 97%